Overcoming barriers to EFL speaking proficiency: A multidimensional analysis of language learning challenges - Ambawani, Suprih; Astasari, Isani; Rukiati, Enik (Politeknik Negeri Jember, 2025)
This study examines the multidimensional barriers affecting the speaking proficiency of English as a Foreign Language (EFL) learners at AKPRIND University, Indonesia. Using a multiple-case study design, the research investigates psychological, linguistic, and pedagogical factors that hinder students’ communication skills. The study focuses on first-year EFL students from diverse academic programs during the 2024/2025 academic year. Findings reveal that speech anxiety, linguistic deficiencies, and traditional teaching methods significantly impede students’ oral communication. Many learners experience high anxiety levels, triggering psychological defence mechanisms that further restrict their speech fluency. The study shows the need for pedagogical transformation, advocating for neurolinguistic strategies, psychological interventions, and interactive teaching methodologies. Key recommendations include the adoption of student-centred communication models, the use of digital tools, and the creation of an inclusive learning environment. This research contributes to the broader discourse on EFL learning by offering insights into the complex interplay between psychological and pedagogical barriers in language learning.